(untitled) (diségno, 2022)
In understanding the multiple relationships between ‘drawing’ and ‘interior design’ we realize the techno-aesthetologic nature of the drawing discipline. Here we propose to do this in the light of two notions that we consider coextensive: the psychological one of ‘affordance’ (James Gibson) and the philosophical one of ‘atmosphere’ (Tonino Griffero) which –according to a particular neuropsychological definition of ‘conscience’ and ‘feeling’ (Antonio Damasio) –practically highlight the ‘what’, the ‘almost what’ and the ‘not-what’ can be represented for descriptive and prescriptive purposes when studying or designing –drawing– an environmental artifact. The crucial question is: ‘how are atmospheres depicted?’ A question that is usually considered pertinent to individual poetics, which cannot be analyzed in structural and morphological terms. Instead, starting from the observation that there are also conventional atmospheres, we propose some features of a method of analysis for these cultural categorizations, a method based on the development of the axiology of the spatial enhancement modes given by Jean-Marie Floch thirty years ago, albeit revising it in the light of more recent acquisitions in the semiotic field and according to the perspectives opened by the Deep Learning computer techniques.